2005
DOI: 10.1242/dev.01813
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear re-organisation of theHoxbcomplex during mouse embryonic development

Abstract: The spatial and temporal co-linear expression of Hox genes during development is an exquisite example of programmed gene expression. The precise mechanisms underpinning this are not known. Analysis of Hoxbchromatin structure and nuclear organisation, during the differentiation of murine ES cells, has lent support to the idea that there is a progressive`opening' of chromatin structure propagated through Hox clusters from 3′to 5′, which contributes to the sequential activation of gene expression. Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
172
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 31 publications
11
172
1
1
Order By: Relevance
“…The role of chromatin in regulating Hox gene transcriptional initiation has recently come under the spotlight through studies showing sequential 3Ј to 5Ј chromatin decondensation of the HoxB cluster during mouse embryonic development (5,50) and regulation of HoxD gene expression through chromatin remodeling during limb development (51) and neural differentiation (33). In this study, we showed that nucleosomes are positioned at the Hoxd4 P1 promoter and are remodeled following RA treatment of P19 cells.…”
Section: Discussionmentioning
confidence: 60%
“…The role of chromatin in regulating Hox gene transcriptional initiation has recently come under the spotlight through studies showing sequential 3Ј to 5Ј chromatin decondensation of the HoxB cluster during mouse embryonic development (5,50) and regulation of HoxD gene expression through chromatin remodeling during limb development (51) and neural differentiation (33). In this study, we showed that nucleosomes are positioned at the Hoxd4 P1 promoter and are remodeled following RA treatment of P19 cells.…”
Section: Discussionmentioning
confidence: 60%
“…What determines which RAresponsive genes are available to be expressed at a given time is the subject of ongoing studies. Recent work has shown that, within a Hox cluster, the timing of hindbrain expression may be regulated by the progressive opening of chromatin rather than the local accumulation of active transacting factors (Chambeyron et al, 2005).…”
Section: Implications For the Regulation Of Retinoic Acid During Hindmentioning
confidence: 99%
“…In mammalian systems, transcription-related chromatin decondensation has been observed in a number of artificial gene clusters, in highly transcribed chromosomal regions and for clusters of functionally related genes that are coordinately regulated during development or between different cells types, such as the Hoxb locus (Tumbar et al, 1999;Tsukamoto et al, 2000;Volpi et al, 2000;Williams et al, 2002;Chambeyron and Bickmore, 2004;Janicki et al, 2004;Chambeyron et al, 2005;Sproul et al, 2005;Morey et al, 2007). In plants, genes are normally considered to be randomly distributed throughout the genome, with the obvious exception of groups of physically linked genes that share sequence homology and that have arisen through tandem gene duplication (e.g., gene-for-gene type disease resistance genes) (Friedman and Baker, 2007).…”
Section: Introductionmentioning
confidence: 99%